Emergency preparedness and rescue in Arctic waters. (April 2021) - Kruke, Bjørn Ivar; Auestad, Ann Christin
Highlights: Remoteness, limited infrastructure and harsh climatic conditions are challenging for maritime activity in the Arctic. Preparedness to meet these challenges must be conducted by the ship owners (relevant knowledge and equipment). Ship crew and passengers are required to handle the initial response. Vessels of opportunity may be vital for a successful response. Availability, mobilization and deployment of professional response agencies is crucial for a successful response. Abstract: On 19 June 1989, the Soviet cruise liner, Maxim Gorkiy hit an ice floe southwest of Spitsbergen, Svalbard. Some 30 years later, on 28 December 2018, the trawler Northguider grounded in the Hinlopenstretet, in Svalbard. In both cases, all crew members and passengers were rescued in dramatic operations. The Arctic waters are challenging for safe maritime activity, due particularly to the remoteness, limited infrastructure and harsh and dynamic climatic conditions, making preparedness a key factor for maritime safety. In light of these ship accidents and challenges, the aim of this paper is to study the special challenges of operating in Arctic waters and the requirements for preparedness to meet these challenges. When studying preparedness in Arctic maritime operations, we consider both the ship owners' own preparations and the availability of Norwegian government rescue services to provide a prompt and efficient response following a ship accident in Arctic waters. The empirical data stems from research into search and rescue regulations, capabilities and operations in the Arctic region, the SARex reports on search and rescue operations in the Arctic (Solberg, Gudmestad et al. 2016, Solberg, Gudmestad et al. 2017, 2018) and participation in the SARex exercises. Both authors of this paper are affiliated with the Arctic Safety Centre in Longyearbyen, Svalbard. The article starts with a presentation of the Arctic and the challenges of operating in Arctic waters, followed by a presentation of the theoretical framework. After a short methods chapter, we present the findings and discuss them in relation to the preparedness concept. We then provide some conclusions on the challenges of operating in Arctic waters and the preparedness equipment, knowledge and structures to meet these challenges.